THE CONCEPT OF APPLYING LEGAL PROTECTION FOR WITNESSES IN UNCOVERING CORRUPTION CASES BASED ON JUDGE'S DECISION NUMBER 34/PID.SUS-TPK/2020/PN.JKT.PST. - Fransisca Chatharina Yulian; Benny Djaja (LPPM Universitas Ekasakti Padang, 2023)
This study aims to analyze the legal efforts undertaken in the context of protecting witness-victims in corruption cases, particularly related to the return of assets of corruption, based on the judge's decision Number 34/Pid.Sus-TPK/2020/PN.Jkt.Pst concerning the Jiwasraya Case. The focus of this research is to identify and analyze the protective measures provided to witness-victims in order to be able to provide information that supports the asset recovery process. The research method used is a normative approach using laws, regulations, and court decisions as a reference. Data was collected through a literature study and analysis of documents related to the Jiwasraya case and the legal framework related to the protection of victim witnesses. The results of the study show that in the judge's decision, there are legal efforts made to protect witness victims in order to return the assets of corruption. These protection efforts include safeguarding the identity of witnesses, providing physical and psychological protection, as well as granting privileges to witness-victims in giving testimony in court. However, several obstacles were found in efforts to protect victim witnesses. Some of them are intimidation or threats against witness-victims, lack of understanding and awareness about witness protection, and difficulties in providing long-term security guarantees for witness-victims. The conclusion of this study is that legal efforts to protect victims-witnesses in corruption cases are very important in returning the assets of corruption. Effective protective measures can increase the confidence of witness-victims to provide accurate testimony and support a fair and transparent asset recovery process.